Answer:
s₁ = 240,000 km
Step-by-step explanation:
The distance between both the focuses f₁ and f₂ will be the sum of distances of the moon from each focus at a given point. Therefore,
s = s₁ + s₂
where,
s = total distance between the focuses = ?
s₁ = distance between f1 and moon = 200,000 km
s₂ = distance between f₂ and moon = 300,000 km
Therefore,
s = 200,000 km + 300,000 km
s = 500,000 km
Now, when the distance from f₂ becomes 260,000 km, then the distance from f₁(planet) will become:
s = s₁ + s₂
500,000 km = s₁ + 260,000 km
s₁ = 500,000 km - 260,000 km
s₁ = 240,000 km